2021
DOI: 10.1016/j.ijid.2020.10.021
|View full text |Cite
|
Sign up to set email alerts
|

COVID toes: where do we stand with the current evidence?

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
2
39
0
5
Order By: Relevance
“…Many manuscripts tried to speculate different possible direct associations with the virus, but to date, there are no reliable data about this. As we previously reported, the main elements which can justify a correlation with COVID-19 infection are the contemporaneity of CLL outbreak with the pandemic with the out-of-season appearance of this type of lesion, and secondarily, the positivity of anti-SARS-CoV or SARS-CoV-2 immunostaining on histological specimens of CLLs, which would confirm the direct detectability of the virus in the lesions [ 14 , 15 ]. According to some authors, in fact, endothelial damage induced by the viral particles could be the mechanism for the development of chilblains [ 16 , 17 ], even if these are only studies on a limited number of patients which should be confirmed by larger ones.…”
Section: The State Of the Art And Future Perspectivesmentioning
confidence: 75%
See 1 more Smart Citation
“…Many manuscripts tried to speculate different possible direct associations with the virus, but to date, there are no reliable data about this. As we previously reported, the main elements which can justify a correlation with COVID-19 infection are the contemporaneity of CLL outbreak with the pandemic with the out-of-season appearance of this type of lesion, and secondarily, the positivity of anti-SARS-CoV or SARS-CoV-2 immunostaining on histological specimens of CLLs, which would confirm the direct detectability of the virus in the lesions [ 14 , 15 ]. According to some authors, in fact, endothelial damage induced by the viral particles could be the mechanism for the development of chilblains [ 16 , 17 ], even if these are only studies on a limited number of patients which should be confirmed by larger ones.…”
Section: The State Of the Art And Future Perspectivesmentioning
confidence: 75%
“…Considering all of these common clinical, histological, and dermoscopic findings, the main doubt is the correlation between CLLs and COVID-19 [ 14 , 15 ]. Many manuscripts tried to speculate different possible direct associations with the virus, but to date, there are no reliable data about this.…”
Section: The State Of the Art And Future Perspectivesmentioning
confidence: 99%
“…Obwohl während der COVID-19-Pandemie ein gehäuftes Vorkommen von Pernionen berichtet wird, kann in der großen Mehrzahl der Fälle kein direkter Zusammenhang zwischen SARS-CoV‑2 und den Pernionen nachgewiesen werden [ 1 , 3 , 4 ]. Der Zusammenhang von SARS-CoV‑2 und vermehrtem Auftreten von Pernionen bleibt somit eine Beobachtung und belegt keine Kausalität.…”
Section: Diskussionunclassified
“…Positive anti-SARS-CoV/SARS-CoV-2 immunostaining on skin lesions from individuals presenting with chilblain-like lesions appears to show the virus in the skin lesions, but it lacks specificity. 25 On the contrary, Baeck and Herman cite several studies that demonstrate that RT-PCR and anti-SARS-CoV-2 serology were negative in the majority of patients that had chilblain-like lesions, indicating that COVID toes may present without a patient being seropositive for COVID-19. These authors also explored the possibility that COVID toes could be a cutaneous expression of type I interferon (IFN-I) response; however, a lack of other symptoms only raises further questions about this hypothesis.…”
Section: Alternative Theoriesmentioning
confidence: 99%
“…An additional alternative provided by Baeck and Herman is that COVID toes may be related to lifestyle changes during COVID-19 lockdowns, including more sedentary lifestyles and exposure to cold floor surfaces. 25 conclusIon Knowledge of COVID toes may help healthcare workers and the general public recognize and diagnose potential cases of COVID-19, especially in cases with few other symptoms. 26 For example, of the confirmed COVID-19 cases compiled in a dermatological study, 19% of the patients presented with pernio-like lesions without other COVID-19 symptoms present.…”
Section: Alternative Theoriesmentioning
confidence: 99%